Pupilometrie jako bioindikátor úcinku léciv - Matousková, Olga; Slanar, Ondrej; Chytil, Lukás; Perlík, Frantisek (Casopis lekaru ceskych, 2010)
BACKGROUND: Measurement of the size of the pupil is used as a biomarker of drug efficacy, assessing mainly their effect on the central nervous system. The aim of our study was to evaluate sensitivity of various pupilometric parameters as biomarkers of widely used opioid analgesic drug tramadol. METHODS AND RESULTS: Pharmacodynamic action of tramadol drops given orally in standardized dose of 0.7 mg/kg was studied in 60 healthy volunteers. Commercially available infrared pupilometer Pupilscan II was used for the measurements of static and dynamic pupilometric parameters prior the dosing and 2.5 hours afterwards. Drug-induced decreases of the initial diameter (0.49 mm) and final diameter (0.38 mm) were significant in the right eye, as well as in the left eye. Minimal parameters (0.35 mm) and time to minimum (0.03 mm) were significantly lower after tramadol administration in the left and right eye only. CONCLUSIONS: Our results confirm the use of pupilometry as an objective, non-invasive tool for evaluation of pharmacodynamic activity of drugs.
Keywords: dospělí; Female; Analgesics, Opioid; pupila; Adult; mladý dospělý; ženské pohlaví; infračervené záření; lidé; tramadol; Infrared Rays; Pupil; opioidní analgetika; Male; aplikace orální; Young Adult; Tramadol; Administration, Oral; mužské pohlaví; Humans